Comparison of the Impact of Conventional Hemodialysis and Hemodiafiltration Techniques on the Evolution of Certain Mineral Bone Parameters in Chronic Hemodialysis Patients - Slimani, Lamia; Jhilal, Fayssal; Ahid, Samir; Maoujoud, Amr (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective: The aim of this study was to compare the impact of conventional hemodialysis (HDC) and hemodiafiltration (HDF) techniques on the evolution of the parameters of phosphocalcic metabolism in chronic hemodialysis patients. Methods: This is a retrospective, descriptive and analytical study carried out in the hemodialysis center of Agadir medico-surgical center during 2015. The total number of patients is 34, 18 were treated by HDC ie 52.9% of cases. Also, 16 patients underwent HDF, ie 47.1% of cases. With each of the 2 techniques, the following parameters were measured: To assess the PTH level, we performed 3 measurements. To evaluate calcium, phosphorus, albumine and CRP levels, 7 measurements were taken. The data were entered via Excel and analyzed through Jamovi 1.6.9 software. We used the Wilcoxon or the Mann-Whitney test for the means. The factors associated with the variation of the studied parameters were analyzed in univariate and multivariate analyzes using the binary logistic regression model. Results: Our population was made up of 41.2% women and 58.8% men. Their average age was 55 ± 11 years. Also, 82.3% of cases had a normal build, 11.7% were overweight and 6% were moderately obese. The distribution of patients according to the causal nephropathy of chronic renal insufficiency presented a predominance of diabetic nephropathy (32.3%) followed by vascular pathology in 10 patients (29.4%). There was no statistically significant difference in the evolution of the levels of the parameters studied (PTH, calcium, phosphorus, albumin and CRP levels) over time. Univariate analysis showed that only the initial nephropathy factors: other nephropathy-vascular nephropathy (p= 0.028; OR=0.060; IC95% [0.004-0.734]) and diabetic nephropathy-vascular nephropathy (p= 0.011; OR=0.050; IC95% [0.004-0.508]) were associated with the variation of the studied parameters. The same factors also emerge in the multivariate analysis: other nephropathy-vascular nephropathy (p= 0.034; OR=0.044; IC95% [0.002-0.791]) and diabetic nephropathy-vascular nephropathy (p= 0.009; OR=0.032; IC95% [0.002-0.429]). Conclusion: According to our results, it seems that there are no significant differences in the evolution of some mineral bone parameters studied with the HDC and HDF techniques.